Fourier or Taylor?

Calculus Level 5

m = 0 n = 0 m ! n ! ( m + n + 2 ) ! = ? \large \sum _{ m=0 }^{ \infty }{ \sum _{ n=0 }^{ \infty }{ \frac { m!n! }{ { \left( m + n + 2 \right) }! } } } =?

k = 1 1 ( 2 k ) 2 \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { (2k })^{ 2 } } } k = 1 1 k 2 \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ k^{ 2 } } } k = 1 1 ( 2 k 1 ) 2 \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ (2k-1)^{ 2 } } } k = 0 1 ( 2 k + 1 ) 2 \sum _{ k=0 }^{ \infty }{ \frac { 1 }{ { (2k+1 })^{ 2 } } }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Feb 7, 2018

Note that m ! n ! ( m + n + 2 ) ! = Γ ( m + 1 ) Γ ( n + 1 ) Γ ( m + n + 3 ) = 1 m + 1 Γ ( m + 2 ) Γ ( n + 1 ) Γ ( m + n + 3 ) = 1 m + 1 B ( m + 2 , n + 1 ) = 1 m + 1 0 1 x m + 1 ( 1 x ) n d x \begin{aligned} \frac{m! n!}{(m+n+2)!} & = \; \frac{\Gamma(m+1)\Gamma(n+1)}{\Gamma(m+n+3)} \; = \; \frac{1}{m+1} \frac{\Gamma(m+2)\Gamma(n+1)}{\Gamma(m+n+3)} \;= \; \frac{1}{m+1}B(m+2,n+1) \\ & = \; \frac{1}{m+1}\int_0^1 x^{m+1}(1-x)^n\,dx \end{aligned} for any m , n 0 m,n \ge 0 , and hence n 0 m ! n ! ( m + n + 2 ) ! = 1 m + 1 0 1 x m + 1 1 1 ( 1 x ) d x = 1 m + 1 0 1 x m d x = 1 ( m + 1 ) 2 \sum_{n \ge 0} \frac{m! n!}{(m+n+2)!} \; = \; \frac{1}{m+1}\int_0^1 x^{m+1} \frac{1}{1 - (1-x)}\,dx \; = \; \frac{1}{m+1} \int_0^1 x^m\,dx \; = \; \frac{1}{(m+1)^2} making the double sum m , n 0 m ! n ! ( m + n + 2 ) ! = m 0 1 ( m + 1 ) 2 = k 1 k 2 = 1 6 π 2 \sum_{m,n \ge 0} \frac{m! n!}{(m+n+2)!} \; = \; \sum_{m \ge 0} \frac{1}{(m+1)^2} \; = \; \sum_{k \ge 1} k^{-2} \; = \; \tfrac16\pi^2

Jon Haussmann
Feb 7, 2018

We have that n ! ( m + n + 1 ) ! ( n + 1 ) ! ( m + n + 2 ) ! = n ! ( m + n + 2 ) ! [ ( m + n + 2 ) ( n + 1 ) ] = n ! ( m + 1 ) ( m + n + 2 ) ! , \begin{aligned} \frac{n!}{(m + n + 1)!} - \frac{(n + 1)!}{(m + n + 2)!} &= \frac{n!}{(m + n + 2)!} [(m + n + 2) - (n + 1)] \\ &= \frac{n! (m + 1)}{(m + n + 2)!}, \end{aligned} so n ! ( m + n + 2 ) ! = 1 m + 1 ( n ! ( m + n + 1 ) ! ( n + 1 ) ! ( m + n + 2 ) ! ) . \frac{n!}{(m + n + 2)!} = \frac{1}{m + 1} \left( \frac{n!}{(m + n + 1)!} - \frac{(n + 1)!}{(m + n + 2)!} \right).

Hence, following sum telescopes: n = 0 n ! ( m + n + 2 ) ! = n = 0 1 m + 1 ( n ! ( m + n + 1 ) ! ( n + 1 ) ! ( m + n + 2 ) ! ) = 1 ( m + 1 ) ( m + 1 ) ! . \sum_{n = 0}^\infty \frac{n!}{(m + n + 2)!} = \sum_{n = 0}^\infty \frac{1}{m + 1} \left( \frac{n!}{(m + n + 1)!} - \frac{(n + 1)!}{(m + n + 2)!} \right) = \frac{1}{(m + 1) (m + 1)!}. Then m = 0 n = 0 m ! n ! ( m + n + 2 ) ! = m = 0 m ! n = 0 n ! ( m + n + 2 ) ! = m = 0 m ! 1 ( m + 1 ) ( m + 1 ) ! = m = 0 1 ( m + 1 ) 2 = k = 1 1 k 2 . \begin{aligned} \sum_{m = 0}^\infty \sum_{n = 0}^\infty \frac{m! n!}{(m + n + 2)!} &= \sum_{m = 0}^\infty m! \sum_{n = 0}^\infty \frac{n!}{(m + n + 2)!} \\ &= \sum_{m = 0}^\infty m! \cdot \frac{1}{(m + 1) (m + 1)!} \\ &= \sum_{m = 0}^\infty \frac{1}{(m + 1)^2} \\ &= \sum_{k = 1}^\infty \frac{1}{k^2}. \end{aligned}

Some details are uncorrect... ‘ Hence, following sum telescopes: _ ' ,the staff under sigma should be n=0 rather than m=0. And the 4th line from the bottom types the same thing wrong.

Haosen Chen - 3 years, 4 months ago

Log in to reply

Thanks, I have made the corrections.

Jon Haussmann - 3 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...